Dribble drabble : process art experiences for young children - Hill, Deya Brashears (St. Paul, MN : Redleaf Press, 2016)
"Creative art should offer children the opportunities for originality, creativity, fluency, flexibility, and sensitivity. Remember, there is no right or wrong way of doing things in art. This collection of activities focuses on the process and not the finished product, to allow for growth and fun. All activities are easily adaptable for children from age two to eight."--Amazon.
Painting -- Crayons -- Collage and sculpture -- Modeling materials -- Chalk -- Printing -- Just for fun -- Glossary of art terms.
Keywords: Art -- Technique; Creative activities and seat work; CRAFTS & HOBBIES -- Crafts for Children; EDUCATION -- Arts in Education; EDUCATION -- Preschool & Kindergarten; FAMILY & RELATIONSHIPS -- Activities